1999
DOI: 10.2134/jeq1999.00472425002800020025x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Suspended and Colloidal Matter in the Leachate from Lysimeters and its Role in Pesticide Transport

Abstract: The relative importance of suspended (>0.45 µm) and organic colloidal (<0.45 µm) matter in the transport of pesticide through and across a soil was studied by monitoring suspended and colloidal matter from lysimeters over a winter (1994–1995) and relating it to the leaching of pesticides. The major results were: (i) The organic colloidal matter and suspended sediment appeared at different times in the leachate. (ii) The suspended sediment was enriched in total organic carbon (TOC). (iii) The leaching of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 0 publications
3
36
0
Order By: Relevance
“…One possibility is that pesticides are also transported sorbed onto organic colloidal particles, which the solid extractions would detect and ELISA would not. This possibility was suggested by Foster et al (1991) and its role in pesticide transport in clay soils was investigated by Worrall et al (1999) using shallow lysimeters. If this were occurring the methanol extractions would be measuring pesticides sorbed onto colloidal particles of material with much greater adsorption potential than the chalk matrix itself, and whose downward progress has been restricted by the narrow apertures or constrictions of microfractures.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that pesticides are also transported sorbed onto organic colloidal particles, which the solid extractions would detect and ELISA would not. This possibility was suggested by Foster et al (1991) and its role in pesticide transport in clay soils was investigated by Worrall et al (1999) using shallow lysimeters. If this were occurring the methanol extractions would be measuring pesticides sorbed onto colloidal particles of material with much greater adsorption potential than the chalk matrix itself, and whose downward progress has been restricted by the narrow apertures or constrictions of microfractures.…”
Section: Resultsmentioning
confidence: 99%
“…However, this result could be explained by colloids acting as a transport carrier. In fact, a previous study showed that a strongly sorbed pesticide could be transported into subsoil via a colloid-facilitated transport mechanism [34][35][36][37]. In contrast, the sorption capability of STZ and SMT is much less than that of TC and CTC [29,38,39], leading to the expectation that the highest mass of STZ was calculated to be at the very bottom of the soil profile.…”
Section: Mass Balance Analysismentioning
confidence: 99%
“…Mechanical stresses such as wetting/drying cycles (Kaplan et al, 1993), freezing/thawing cycles (Worrall et al, 1999) and moving water impose shear stress; all these processes act on soil particle mobilisation (Ryan et al, 1998;Shang et al, 2008). Experiments conducted by Kjaergaard et al (2004b) and Majdalani et al (2008) showed that the rate of mobilisation is related to the drying intensity i.e.…”
Section: Impact Of Physical and Mechanical Mechanisms On Particle Mobmentioning
confidence: 99%